Smart City Strategy in Urban Development Management: Effectiveness Study in Banjarbaru City - Ambarwati, Riris; Azahrarty, Azahrarty; Amelia, Citra; Suryani, Khalisa Rahmina; Permana, Yudi (International Journal of Economics (IJEC), 2025)
The concept of a smart city has emerged as a key paradigm in modern urban management, particularly in enhancing public service efficiency, governance, and environmental sustainability. This study explores the smart city strategy in the urban development of Banjarbaru City, aiming to evaluate the implementation and effectiveness of related policies and technologies that support digital innovation. Employing a qualitative approach, data were collected through in-depth interviews, field observations, and document analysis involving stakeholders such as local governments, academics, and community members. The findings reveal that smart city initiatives in Banjarbaru have positively impacted public service efficiency, especially in digital governance, technology-based transportation, and urban environmental management. Nonetheless, several challenges persist, including inadequate digital infrastructure, limited public technological literacy, and insufficient readiness of human resources to adopt new technologies. Resistance to change and a lack of system integration across sectors further hinder progress. This study recommends enhancing data-driven policy formulation, strengthening technological infrastructure, improving human resource capacity, and fostering collaboration between government, private sectors, and the community to support digital transformation. Moreover, innovative financing models such as public-private partnerships (PPP) and green bonds are proposed as viable strategies to accelerate sustainable smart city development. The study also highlights the need for future research on evaluating the sustainability of smart cities, developing measurable performance indicators, and mitigating risks in urban technological implementation. With an inclusive and innovation-oriented approach, Banjarbaru demonstrates significant potential to become a model smart city that is efficient, sustainable, and adaptive to contemporary urban challenges.